Agricultural Trade and Protection in Asia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The study reveals agricultural import restrictions are widely applied in Asia, but that Japan and Korea impose lower average tariffs and nontariff barriers with less frequency than most Asian countries. It also finds several low and middle-income countries enforce relatively low protection for basic foodstuffs, while high-income countries tend to impose relatively high protection for foods. Finally, commodity patterns of trade and protection suggest scope exists for successful reciprocal negotiations to liberalize agricultural trade mainly between low and middle-income Asian countries. Though similar gains might be achieved by unilateral liberalization, reciprocal negotiations are more feasible politically and, on a most-favored-nation basis, would imply greater trade expansion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet